PENGARUH STRUKTUR KEPEMILIKAN KELUARGA TERHADAP KINERJA PERUSAHAAN PERUSAHAAN PROPERTY DAN REAL ESTATE - Liana Dewi; Juniarti Juniarti Juniarti (Business Accounting Review, 2017)
The majority of companies listed on the BEI are family companies, where family companies have advantages and disadvantages that affect the company's performance of the companies. According to many previous researches about the influence of family control, there were still many unconsistent result. This study aimed to know the influence of family control on probability. Profitability was measured by using ROA (Return on Asset). The control variables use good corporate governance, intensity of competition, and sale growth. The samples use in this research were firms in sector property and real estate industry which fulfilled certain criteria and analysed using multiple regression analysis.